Kajian Literatur Sistematis Penelitian Religiusitas di Indonesia: Istilah, Definisi, Pengukuran, Hasil Kajian, serta Rekomendasi - Subhan El Hafiz; Yonathan Aditya (Konsorsium Psikologi Ilmiah Nusantara, 2021)
Religiosity in Indonesia is an interesting subject to be explored and thousands of studies have been carried out but very few literature studies have attempted to compile the studies in such away to give a more comprehensive understanding of religiosity in Indonesia. This study aims to find an understanding of religiosity in Indonesia from various studies conducted in Indonesia using systematic literature review techniques. Utilizing the Google Scholar database and its tools, data is obtained and reduced to enable analysis. The result revealed that the concept of religiosity in Indonesia was unique in terminological aspect, definition, and measurement. The implications of the findings are discussed